Sustainable catalysis : energy-efficient reactions and applications - Luque, Rafael; Lam, Frank Leung-Yuk. ([Place of publication not identified] : Wiley-VCH, 2017)
Highlighting sustainable catalytic processes in synthetic organic chemistry, this useful guide places special emphasis on catalytic reactions carried out at room temperature. It describes the fundamentals, summarizes key advances, and covers applications in the field of organic synthesis, biomass conversion, and pollution control. Throughout, the latest research from various disciplines is combined, such as homogeneous and heterogeneous catalysis, biocatalysis, and photocatalysis. The book concludes with a chapter on future trends and energy challenges for the latter half of the 21st century and two case studies. With its multidisciplinary approach this is an essential reference for academic and industrial researchers in catalysis science aiming to design more sustainable and energy-efficient processes.
1) Introduction to Room-Temperature Catalysis; 2) Functionalized Ionic Liquid-based Catalytic Systems with Diversified Performance Enhancements; 3) Heterogeneous Room-Temperature Catalysis -; Nanomaterials; 4) Biocatalysis at Room Temperature; 5) Room Temperature Catalysis Enabled by Light; 6) Heterogeneous Room-Temperature Catalysis: Biocatalysis; 7) Palladium-Catalyzed Cross-Coupling in Continuous Flow at Room and Mild Temperature; 8) Catalysis for Environmental Applications; 9) Challenges in the 21st Century and Future Development in Room-Temperature Catalysis; 10) Case Study 1 -; Magnetic Pd Catalysts for Benzyl Alcohol Oxidation to Benzaldehyde; 11) Case Study 2 -; Synthesis of Hydrothermally Stable Functional Materials for Sustainable Conversion of Biomass to Furan Compounds.
Print version record.
Keywords: Catalysis; Green chemistry; Electronic books